Probabilistic analysis of structural properties distribution simulation for composite nanoparticles formed in gas phase - Vakhrouchev, Alexandr Vasilievich; Fedotov, Alexey Yurievich (Computational Continuum Mechanics, 2008)
The mathematical model of condensation processes of composite nanoparticles from a gas phase is submitted. Calculation results of formation composite nanoparticles from silver and copper at vacuum evaporation and condensation are obtained. The basic nanoparticles properties are calculated. Numerical simulation of nanoparticles forming process is executed many times. The series of selective nanoparticles parameters such as number of nanoparticles in volume, its average diameter, average density and silver mass portion in nanoparticles are obtained. Lows of nanoparticles properties distribution are checked by means of Pirson criterion and statistic function. The analysis of evaluative parameters is executed for suggesting theoretical lows.